Self-Regulation Training, Labor Market Reintegration of Unemployed Individuals, and Locus of Control - Evidence from a Natural Field Experiment - Eva M. Berger; Guenther Koenig; Henning Mueller; Felix Schmidt; Daniel Schunk (Center for Economic Studies and ifo Institute (CESifo), 2016)
Recent evidence suggests that self-regulation plays an important role for labor market success. We conducted a randomized natural field experiment embedded in an existing labor market reactivation program to examine the effect of a self-regulation training on long-term unemployed individuals. First, we find a positive treatment effect on the quality of submitted CVs. Second, there is no overall treatment effect on (short-term) labor market reintegration, but heterogeneous effects with respect to participants' Locus of Control that are consistent with psychological theory. The low costs of our intervention suggest high individual and social rates of return from a roll-out to other programs.
Keywords: C93; J24; J64; 330; active labor market policy; natural field experiment; Germany; labor market reintegration; unemployment; reemployment; self-regulation; locus of control; non-cognitive skills